2006
DOI: 10.1124/jpet.106.111153
|View full text |Cite
|
Sign up to set email alerts
|

Marked Insulin Resistance in Obese Spontaneously Hypertensive Rat Adipocytes Is Ameliorated by in Vivo but Not in Vitro Treatment with Moxonidine

Abstract: The obese spontaneously hypertensive rat (SHROB) is a model of marked insulin resistance with normoglycemia. We sought to determine whether insulin resistance extends to adipocytes and the impact of an insulin-sensitizing imidazoline, moxonidine (4 mg/kg/days for 21 days). Gonadal adipocytes were isolated from SHROB and lean spontaneously hypertensive rat (SHR) littermates. In lean SHR adipocytes, Akt activation by 100 nM insulin peaked at 3 min at 25-fold, whereas SHROB adipocytes showed only 4-fold activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
0
9
0
2
Order By: Relevance
“…The following transduction cascade can therefore be proposed: I 1 R ¡ inactivation of adenylate cyclase ¡ 2cAMP ¡ inactivation of SIRT1/ FOXO1 ¡ activation of PPAR␥ ¡ 1adiponectin synthesis. The direct peripheral modulation of adiponectin and AMPK signaling highlighted in the present study probably contributes to the overall beneficial effect on insulin resistance of sympathoinhibitory antihypertensive agents (39,43) and I 1 R ligands (7). Nevertheless, additionnal non-adiponectin mechanisms of action cannot be ruled out.…”
Section: Discussionmentioning
confidence: 70%
“…The following transduction cascade can therefore be proposed: I 1 R ¡ inactivation of adenylate cyclase ¡ 2cAMP ¡ inactivation of SIRT1/ FOXO1 ¡ activation of PPAR␥ ¡ 1adiponectin synthesis. The direct peripheral modulation of adiponectin and AMPK signaling highlighted in the present study probably contributes to the overall beneficial effect on insulin resistance of sympathoinhibitory antihypertensive agents (39,43) and I 1 R ligands (7). Nevertheless, additionnal non-adiponectin mechanisms of action cannot be ruled out.…”
Section: Discussionmentioning
confidence: 70%
“…Our present results showed that like moxonidine, S43126 also cause increased phosphorylation of ERK and PKB. Ernsberger's lab showed that in adipocytes isolated from SHROB treated with moxonidine in vivo, there was an improved response to insulin, both in terms of PKB activation and facilitation of glucose uptake [26]. Since receptors are defined by their signaling pathways, our data suggest that S43126 is an agonist at the imidazoline binding site.…”
Section: Effects Of S43126 On Erk1/2 and Pkb Phosphorylationmentioning
confidence: 60%
“…Moxonidine has been shown to ameliorate elements of metabolic syndrome in both animals and humans. Moxonidine treatment improved glucose disposal and increased insulin-stimulated phosphorylation of key insulin signaling intermediates [6,8,10,26] in the spontaneously hypertensive rat (SHROB; Koletsky rat) model of metabolic syndrome. The beneficial effects of moxonidine on elements of the metabolic syndrome extend to humans with similar disorders.…”
Section: Introductionmentioning
confidence: 99%
“…In obese spontaneously hypertensive rat adipocyte that chronic, but not acute, selective moxonidine treatment partially restores insulin sensitivity [49]. Moxonidine reduced blood pressure associated with improving insulin sensitivity in obese hypertensive patients [50].…”
Section: Pharmacological Treatments For Hypertension In Obesitymentioning
confidence: 96%